Can the ‘Other’ Frame Back in Tourism Studies? - Sarani Pitor Pakan (Via@)
This essay began with the confusion and question about the very rare presence of non-Western tourist in the analysis of tourism. Then, I experimented to respond to such rarity by showcasing the photographs of Indonesian students-cum-tourists in the West. This essay is basically a reflection on my own experiment to respond to the Western-biased, Eurocentric, and colonial knowledge production in tourism studies. I found myself, who initially aimed to offer reverse South-to-North tourist/photographic framings, trapped in the question concerning whether non-Western tourism researchers are really able and need to frame back and talk back in academia. While the experiment itself might not be able to seriously challenge the Eurocentric knowledge production in tourism studies, I found it useful as a pedagogy of self-reflection through which non-Western tourism researcher, like me, can resituate her/his postcolonial being, thinking, and sensing and be an initial seed of future decolonial praxis.